(NsTRUKTURA I FUNKCIONIROWANIE @VNOTAEVNYH GEOSISTEM pRIIRTY[XQ (B/s - (NaNTONENKO(B, (NaNTONINA mIHAJLOWNAs; (NkUSTOW(B, (N`RIJ wASILXEWI^s; (NlAJWINX[(B, (NmARIS qNOWI^s; (NsNYTKO(B, (Nw(B.(Na(B.s; (NiN(B-(NT GEOGRAFII sIBIRI I dALXNEGO wOSTOKA so an sssrs ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1982)
(NbIBLIOGR(B.: (NS(B. 117-120s
Keywords: (NfIZI^ESKAQ GEOGRAFIQs